Response of cumin (Cuminum cyminum L.) cultivars to nutrient management practices in arid zone of Rajasthan, India - A V Rao, Raj Singh, (Journal of Spices and Aromatic Crops, 2006)
A field study was conducted at Satheen Village (Rajasthan) to investigate different nutrientmanagement practices on the production of two cultivars of cumin (Cuminum cyminum) inarid zone. Cultivar RZ-19 was superior to local cultivar with respect to seed yield (21.5%higher) and its attributes. The net returns and benefit:cost ratio obtained with RZ-19 wasmuch higher compared to that of local variety. All the nutrient management practices re-corded significantly higher yield and its attributes over control. However, the maximumseed yield of 586 kg ha-1 was recorded with integrated nutrient management practices in-volving tumba cake (Citrullus colocynthis) with 50% recommended dose of fertilizers andapplication of bio-fertilizer (Azotobacter chroococcum + phosphate solubilizing bacteria), whoseyield was at par with that of integrated nutrient management practices involving applica-tion of 5 t farm yard manure. Maximum returns (Rs. 20,300/-) and benefit:cost ratio (2.51)was obtained in integrated nutrient management practices involving application of 5 t offarm yard manure.